Teach Yourself VISUALLY MacBook Pro & MacBook Air - Guy Hart-Davis (author) (Wiley-Blackwell, 2022)
Get up to speed with your new MacBook Pro or MacBook Air faster than you thought possible In Teach Yourself VISUALLY: MacBook Pro & MacBook Air, technology educator extraordinaire and bestselling author Guy Hart-Davis delivers a highly illustrated and easy-to-follow guide to using your MacBook Pro or MacBook Air with macOS Monterey. In the book, you'll get up and running quickly whether you're brand new to computers or just transitioning from an older Mac or a PC. With the graphics-driven approach used successfully by tens of thousands of readers of the Teach Yourself VISUALLY series, you see exactly what each step of instruction should look like on your own screen and can follow--step-by-step--through the installation process, file management, email, and messaging, and much more. You'll also: Become expert with the latest macOS version--Monterey--and the newest features that enable you to make the most of your MacBook and the Internet Learn exactly how to handle the most common and useful everyday tasks you need to get stuff done Glean valuable customization tips to make your MacBook work just the way you prefer Teach Yourself VISUALLY: MacBook Pro & MacBook Air skips confusing tech jargon in favor of clear pictures, simple instructions, and stepwise guidance that will give you a flying start to using your new MacBook, regardless of your experience level.